2021
DOI: 10.1007/s11469-021-00657-1
|View full text |Cite
|
Sign up to set email alerts
|

A Psychometric Analysis of Fear of COVID-19 Scale in India

Abstract: COVID-19 has had a serious negative impact on the mental health of people around the world. The present study analyses the psychometric properties of Fear of COVID-19 Scale (FCV-19S) in the Indian context. The study checks the one-factor and two-factor structures of the measure. Data were collected from 992 respondents from India. Structural equation modeling was performed to check the construct validity after checking the factorial validity, reliability, and model fit. Both one-factor and two-factor models ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…Possible scores ranged from 8 to 40 and were tabulated by summing the responses to each item, with higher scores indicating greater FOC. The scale has been used in India previously with good internal consistency (Bharatharaj et al, 2021;Lathabhavan, 2021) and demonstrated high internal consistency in the present study (Cronbach's alpha [α] = .92).…”
Section: Fear Of Coronavirus (Foc)mentioning
confidence: 70%
“…Possible scores ranged from 8 to 40 and were tabulated by summing the responses to each item, with higher scores indicating greater FOC. The scale has been used in India previously with good internal consistency (Bharatharaj et al, 2021;Lathabhavan, 2021) and demonstrated high internal consistency in the present study (Cronbach's alpha [α] = .92).…”
Section: Fear Of Coronavirus (Foc)mentioning
confidence: 70%
“…[7,9,41,43,48,49,52,56,57,63,68] Conversely, the results are inconsistent to that of other studies where 2 factor models, emotional and physical response, were found to be better fit in the bifactorial structure than that of the unidimensional structure found in the current study. [6,37,47,51,55,62,63,69,70] It is also important to note that in other studies, FCV-19s was found to have 1 factor and 2 factor models. [37,55,70] Cronbach's alpha score tested the reliability of FCV-19s and found good reliability (α = 0.884).…”
Section: Discussionmentioning
confidence: 84%
“…Although the factor structure originally proposed by Ahorsu et al (2020) was a one-factor congeneric model, here we have included the one-factor τ-equivalent model to check for the appropriateness of reporting the α coefficient as a reliability index for the FCV-19S, since only the one-factor τ-equivalent model meets the underlying assumptions of the α coefficient, and this reliability index has been reported in the majority of the studies where the scale was used and was also the main effect size index synthesized in the study of Blázquez-Rinco ´n, Durán and Botella (2022). At the same time, several studies informed that a two-factor model yields a better fit to the data than the original one-factor congeneric model (Andrade et al, 2022;Barrios et al, 2021;Bellamkonda & Pattusamy, 2022;Caycho-Rodríguez, Valencia, et al, 2022;Fatfouta & Rogoza, 2021;Iversen et al, 2022;Lathabhavan, 2023;Magano et al, 2021;Midorikawa et al, 2021;Reznik et al, 2021), we, therefore, considered it necessary to compare the fit between these two measurement models.…”
Section: Discussionmentioning
confidence: 95%
“…The main limitations of our work come from the novelty of the techniques used. In the first place, we left out from the analyses one study that met the selection criteria (Lathabhavan, 2023) because of statistical reasons (nonpositive definite matrices cannot be integrated). This is something that would have not happened in a traditional meta-analysis, in which the statistics of interest from all selected primary studies would have been pooled.…”
Section: Discussionmentioning
confidence: 99%